Modified Na‐Montmorillonite With Quaternary Ammonium Salts: Application for Removal of Salicylic Acid From Aqueous Solutions. Issue 8 (19th May 2015) - Meng, Zilin; Lv, Fengzhu; Zhang, Yihe; Zhang, Qian; Zhang, Zhilei; Ai, Shutao
<x xml:space="preserve">Abstract</x> Na‐montmorillonite (Mont) modified by cetyltrimethylammonium bromide (CTAB‐Mont) and tetramethylammonium bromide (TMAB‐Mont) was used to remove salicylic acid (SA) under batch kinetic and different solution conditions. The adsorption capacity of CTAB‐Mont (202.1 mg/g) was larger compared to TMAB‐Mont (10.2 mg/g) under the same conditions. Characterization of the modified Monts was performed with X‐ray diffraction, Fourier transform IR spectroscopy, elemental analyses, zeta potential, and molecular simulation by the Forcite module of Materials Studio 5.0 software. The Freundlich isotherm and the pseudo‐second‐order kinetic model fit the experimental data well. The results indicated that the adsorption mechanism of SA absorbed on CTAB‐Mont is based on strong interaction of SA with the exposed siloxane surface and also on π–π interaction of SA with the absorbed SA molecules in the interlayer. The arrangement of molecules in the interlayer was studied by molecular simulation and the results were consistent with the experimental results. The consistency verified the hypothesized adsorption mechanism.